Perbudakan Modern Dalam Dunia Kerja - Isma Ulyana Arifatun Nasekhah; Lutfiyah Lutfiyah (Jayapangus Press, 2026)
This study analyzes how modern slavery in Indonesia's manufacturing sector emerged through forms of exploitation disguised in formal labor relations, although the labor law framework has been comprehensively drafted. Competitive pressures in global supply chains, work flexibility through contracting and outsourcing systems, and inequality of bargaining positions between workers and companies create working conditions that are vulnerable to exploitative practices. This study aims to identify modern forms of slavery in the context of factory work, analyze the structural factors that perpetuate it, as well as assess the policy implications needed to strengthen worker protections. The research uses a qualitative approach with a case study design in three textile and garment manufacturing industry clusters, footwear, and electronics. Data was collected through in-depth interviews with 45 informants that included workers, company management, trade unions, NGO activists, and government officials, as well as an analysis of policy and corporate documents. Thematic analysis is used to identify patterns of exploitation and structural vulnerabilities that emerge in the context of the industry. The results of the study show four main forms of modern slavery practices: economic exploitation, restriction of freedom, vulnerability and dependence, and dehumanization. These practices are reinforced by unequal labor market structures, labor flexibility, and cost pressures from global buyers. In addition, female workers and low-educated workers were found to have higher levels of vulnerability than other groups. Document analysis also shows a significant gap between corporate social responsibility rhetoric and actual working conditions. The study concludes that modern slavery in the manufacturing industry operates through complex structural mechanisms that require strengthening law enforcement, revision of the employment contract system, and multi-stakeholder collaboration. These findings underscore the urgency of labor protection reforms amid economic and technological changes.